Systemic interventions - Schlippe, Arist von; Schweitzer, Jochen (Vandenhoeck Ruprecht, 2015)
Systemic thinking has opened up further areas of specialization from one-on-one and couples therapy to clinical supervision and organizational development. Systemic intervention sees a problem as an incident involving a number of different, interacting individuals. In this sense, conflict, problems and occurrences are viewed and treated within the social context. This comprehensive introduction contains many examples and detailed suggestions for a practical approach to directed conversation. 1977-1981: Tätigkeit in Kinder- und Jugendpsychiatrie 1981-2005 Wissenschaftlicher Mitarbeiter am Fachbereich Psychologie der Universität Osnabrück Seit 1986: Lehrtherapeut und Lehrender Supervisor am am IF Weinheim, Institut für systemische Ausbildung und Entwicklung
Description based upon print version of record
Keywords: Systemische Therapie